Software at Scale. - Cerf, Vinton G. (Communications of the ACM, 2013)
The article focuses on developments related to computer programming as of December 2013. It highlights the implications of the growing number of programmable devices and appliances including their need for software to be able to function. The author discusses the development of the VisiCalc spreadsheet program by programmers Dan Bricklin and Robert Frankston 35 years ago including how it helped transform the Apple II desktop computer into a business tool.